THE PRACTICE-ORIENTED MODEL OF TRAINING A FOREIGN LANGUAGE PHILOLOGIST AT THE UKRAINIAN UNIVERSITY - Khalymon, I. Y.; SLYVKA, Valentyna; TEZIKOVA, Svitlana (ISRES Publishing, 2024)
This chapter provides an in-depth analysis of the practice-oriented experience of training students in a specialized bachelor's degree program in Philology with a specialization in Germanic Languages and Literatures (including Translation) - English and German Languages at Nizhyn Mykola Gogol State University in Ukraine. Embracing the competency approach, which focuses on the practical application of knowledge and skills, our training of specialists is designed to increase the time dedicated to fulfilling professionally aimed tasks grounded in fundamental knowledge, practical skills, and values. In the face of rapid changes in the language industry, including the rise of artificial intelligence and machine translation, the need to train specialists in environments mirroring actual work conditions has never been more pertinent. The competency approach ensures that our students acquire theoretical knowledge and develop the practical skills and professional values necessary for success in the industry. Our educational program, Germanic Languages and Literatures (including Translation) - English and German Languages at Nizhyn Mykola Gogol State University significantly emphasises practical training. A total of 24 credits are dedicated to field experience, spread across all four years of study. This practical approach, from introductory practice in the first year to translation work placement practice in the fourth year, ensures our students are well prepared for the real-world challenges of their chosen profession. The article also introduces the sequential program of practical training for philology students, describing the tasks and contents and the means to ensure continuity and sequence in forming professional competencies in class and extracurricular activities. This includes participation in translation contests, translation societies, and meetings with specialists in this field, who provide real-world insights and feedback on students' work.
Keywords: practice-oriented experience; competency approach; Philology with a specialization in Germanic Languages and Literatures (including Translation); educational program; Ukraine